If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 37x + 20 = 6(6x + 7) Reorder the terms: 20 + 37x = 6(6x + 7) Reorder the terms: 20 + 37x = 6(7 + 6x) 20 + 37x = (7 * 6 + 6x * 6) 20 + 37x = (42 + 36x) Solving 20 + 37x = 42 + 36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36x' to each side of the equation. 20 + 37x + -36x = 42 + 36x + -36x Combine like terms: 37x + -36x = 1x 20 + 1x = 42 + 36x + -36x Combine like terms: 36x + -36x = 0 20 + 1x = 42 + 0 20 + 1x = 42 Add '-20' to each side of the equation. 20 + -20 + 1x = 42 + -20 Combine like terms: 20 + -20 = 0 0 + 1x = 42 + -20 1x = 42 + -20 Combine like terms: 42 + -20 = 22 1x = 22 Divide each side by '1'. x = 22 Simplifying x = 22
| x+2/x=x/3 | | 4n+22.95=2n-22.95*3 | | 3-4(x-2)-4=-3(x+1)-6 | | 6x-9x+2=x-8+10 | | 2n+3=3n-2 | | 50+70+90= | | 2n-3=3n-2 | | x^4+2x^3-9x^2-10x+20=0 | | 26x+8=5(5x+7) | | 10x-0.5= | | 18y=9+0 | | 5n+6=6n-994 | | 7x-26=x+22 | | 5n+6=994 | | ln(9)+ln(x^2)=9 | | 8x=94 | | 2tan(2x)+3tanx+1=0 | | 24+8v=16v | | (g+3)*(g+3)-1=6*(g+4)+18 | | 27-y=2y | | 30k-48-20=11(2k-3)+3k | | 2v+24=6v | | x--3=5 | | (f+4)*(f-4)=f*(f-6)+8*4 | | X^3-(27i)=0 | | 9e-6*[(3e+4)-(5e-7)]=18-4*[3*(2e-5)-9] | | 0.12+0.45=4.30 | | 15x+6y=360 | | x=7-7 | | x=7-0 | | Ln(6x-5)=6 | | 7.7x-4=6.7x |